Multivariate approach in the selection of superior soybean progeny which carry the RR gene - Dallastra, Anderson [UNESP]; Unêda-trevisoli, Sandra Helena [UNESP]; Ferraudo, Antonio Sergio [UNESP]; Di Mauro, Antonio Orlando [UNESP] (Universidade Federal do Ceará, 2014)
Efficiency in the use of genetic variability, whether existing or created, increases when properly explored and analysed. Incorporation of biotechnology into breeding programs has been the general practice. The challenge for the researcher is the constant development of new and improved cultivars. The aim of this experiment was to select progenies with superior characteristics, whether or not carriers of the RR gene, derived from bi-parental crosses in the soybean, with the help of multivariate techniques. The experiment was carried out in a family-type experimental design, including controls, during the agricultural year 2010/2011 and 2011/2012 in Jaboticabal in the Brazilian State of São Paulo. From the F3 generation, phenotypically superior plants were selected, which were evaluated for the following traits: number of days to flowering; number of days to maturity; height of first pod insertion; plant height at maturity; lodging; agronomic value; number of branches; number of pods per plant; 100-seed weight; number of seeds per plant; grain yield per plant. Given the results, it appears possible to select superior progeny by principal component analysis. Cluster analysis using the K-means method links progeny according to the most important characteristics in each group and identifies, by the Ward method and by means of a dendrogram, the structure of similarity and divergence between selected progeny. Both methods are effective in aiding progeny selection.

A eficiência do aproveitamento da variabilidade genética, existente ou criada, aumenta quando esta é devidamente explorada e analisada. A incorporação de eventos biotecnológicos aos programas de melhoramento tem sido uma prática usual. O pesquisador tem como desafio, o desenvolvimento constante de novas e melhores cultivares. O objetivo deste experimento foi selecionar progênies com caracteres superiores e portadoras ou não do gene RR, oriundas de cruzamentos bi-parentais em soja, com o auxílio de técnicas multivariadas. O experimento foi conduzido em delineamento experimental do tipo famílias com testemunhas intercaladas no ano agrícola 2010/2011 e 2011/2012 em Jaboticabal-SP, Brasil. Na geração F3, foram selecionadas plantas fenotipicamente superiores, sendo estas avaliadas para os caracteres: número de dias para o florescimento, número de dias para a maturidade, altura de inserção da primeira vagem, altura de planta na maturidade, acamamento, valor agronômico, número de ramos, número de vagens por planta, peso de 100 sementes, número de sementes por planta e produção de grãos por planta. Diante dos resultados, verifica-se a possibilidade de selecionar progênies superiores através da análise de componentes principais. A análise de agrupamentos, através do método de K-means, une as progênies de acordo com os caracteres de maior importância em cada grupo e, através do método de Ward, identificou por meio do dendrograma a estrutura de similaridade e divergência entre as progênies selecionadas. Os dois métodos são eficientes no auxilio da seleção de progênies.
Abordagem multivariada na seleção de progênies de soja superiores e portadoras do gene RR
Keywords: Glycine max; Variabilidade genética; Análise multivariada; Glycine max; Genetic variability; Multivariate analysis